2020
DOI: 10.1186/s13071-020-3884-y
|View full text |Cite
|
Sign up to set email alerts
|

First detection of Enterocytozoon bieneusi in whooper swans (Cygnus cygnus) in China

Abstract: Background: Enterocytozoon bieneusi is a parasite that infects humans and a wide range of other animals. The large migratory waterfowl, the whooper swan (Cygnus cygnus), travels through many cities during its migration and can spread parasites. Despite receiving increasing attention worldwide, there have been no reports of E. bieneusi infection occurring in C. cygnus. Therefore, this study aims to assess the prevalence and genetic characteristics of E. bieneusi in C. cygnus in Sanmenxia, China.Methods: Altoget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…PtEbI, PtEbVII) (from Peru and Portugal) and Henan-III (from Malaysia and China) have been spread across limited geographical area as well as small number of E. bieneusi -infected human cases compared with genotypes D and Type I [ 34 36 ]. Meanwhile, genotype Peru 6 has been identified in sheep, goats, reindeers, and wastewater [ 37 – 40 ], whereas genotype Henan-III has been found in NHPs, pet snakes, pigs, and birds in China [ 41 – 44 ]. Therefore, the above shreds of evidence suggest the possible zoonotic transmission of these genotypes from the wild rhesus macaques to humans.…”
Section: Discussionmentioning
confidence: 99%
“…PtEbI, PtEbVII) (from Peru and Portugal) and Henan-III (from Malaysia and China) have been spread across limited geographical area as well as small number of E. bieneusi -infected human cases compared with genotypes D and Type I [ 34 36 ]. Meanwhile, genotype Peru 6 has been identified in sheep, goats, reindeers, and wastewater [ 37 – 40 ], whereas genotype Henan-III has been found in NHPs, pet snakes, pigs, and birds in China [ 41 – 44 ]. Therefore, the above shreds of evidence suggest the possible zoonotic transmission of these genotypes from the wild rhesus macaques to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they have also been found in some animals from China. For instance, genotype KIN-1 has been found in pigs, cattle, deer, and goats (21)(22)(23)(24); genotype CHN4 in calf and coypus (25,26); and genotype Henan-III in NHPs, pet snakes, pigs, and birds (6,(27)(28)(29). The above results indicate that masked palm civets could harbor the different zoonotic genotypes.…”
Section: Discussionmentioning
confidence: 85%
“…Genotype XJP-II was previously found in pigs in Xinjiang ( Li D. F. et al., 2019b ), and NCF2 was also identified in farmed foxes ( Vulpes lagopus ) ( Zhang et al., 2016 ; Ma et al., 2020 ) and raccoon dogs ( Nyctereutes procyonoides ) ( Xu et al., 2016 ) in China, Kangaroo in Australia ( Zhang Y. et al., 2018 ). Genotypes EbpC, EbpA, and D were frequently found in humans and a broad range of animals ( Wang et al., 2013 ; Liu et al., 2017 ; Qi et al., 2018 ; Zhang X. X. et al., 2018 ; Zou et al., 2018 ; Wang H. et al., 2020 ; Wang Y. et al., 2020 ; Yu et al., 2020 ). The results showed that natural transmission of E. bieneusi among rodents, humans and many other animals may occur.…”
Section: Discussionmentioning
confidence: 99%